Analysis of the correlation between different forms of access to water and cases of gastroenteritis hospitalization in the territory of Médio Piranhas, Paraíba State, Brazil - Silva Filho, José Adalberto da; Araújo, Sayonara Costa de; França, Kevison Romulo da Silva; Silva, Jéssica de Andrade Gomes; Nogueira, Virgínia de Fátima Bezerra (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2016)
Drinking water has a direct influence on people's well-being, since this resource can transmit various diseases. This research proposes the diagnosis of access to water in the territory of Médio Piranhas, located in semiarid portion of Paraíba State, Brazil. The premise is based on the number of gastroenteritis hospitalization accounted for the Department of Health System Information. The authors selected the municipalities and collected secondary data from the Brazilian Institute of Geography and Statistics. The paper became evident the relationship between the form of access to water and the cases of gastroenteritis hospitalization. The results indicated that 71,75% of residences in the territory receive a water supply service. It was also observed 2.725 cases of gastroenteritis hospitalizations between 2010 and 2015, which provided a correlation of approximately 39%, showing that more investments in infrastructure need to be made in order to improve the health and well-being of the population, and consequently reduce the chain of transmission of water-related diseases. Análise da correlação entre diferentes formas de acesso à água e os casos de internações por gastroenterite no território do Médio Piranhas-PB Resumo: A água de consumo exerce influência direta no bem-estar da população, uma vez que este recurso pode ser um veículo transmissor de diversas enfermidades. Esta pesquisa propõe o diagnóstico do acesso à água no território do Médio Piranhas, localizado no semiárido paraibano. A premissa encontra fundamento no grande número de internações por gastroenterite contabilizado pelo Departamento de Informática do Sistema Único de Saúde. Foram selecionados os municípios e coletados dados secundários do Instituto Brasileiro de Geografia e Estatística. O trabalho tornou notória a relação existente entre a forma de acesso à água e os casos de internação pela enfermidade adotada. Os resultados indicaram que 71,75% dos domicílios do território constam com uma cobertura por um sistema de tratamento e abastecimento de água. Foram contabilizados 2725 casos de internações por gastroenterite no período de 2010 a 2015, o que forneceu uma correlação de aproximadamente 39%, evidenciando que mais investimentos em infraestrutura precisam ser feitos, visando melhorar a saúde e bem-estar da população, além de, consequentemente, reduzir a cadeia de transmissão das doenças de veiculação hídrica.